The effects of adding protein to dry-rolled sorghum grain fattening rations - Smith, E.F.; Richardson, D.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Previous work (Bulletin 447) indicated that sorghum grain fattening rations supplemented with 0.5 pound per head per day of soybean oil meal produced gains minimal in efficiency and carcasses equal to those from heifers fed 1 pound of protein per had daily. With each increase of 0.5 pound of protein (0, 0.5, and 1.0) came a 0.20-pound increase in average daily gain, an increase in feed efficiency, and an increase in profit over feed cost.
Keywords: Beef; Protein; Sorghum grain; Soybean meal